HIGHLIGHTING FREQUENT ACADEMIC IDIOMS BETWEEN AMERICAN AND BRITISH PEOPLE: A CORPUS-BASED STUDY - C. I Wayan Eka Budiartha (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2015)
Knowledge of idioms in academic English is required to improve student’s academic writing and critical thinking skill, however many language teachers and instructors find it difficult generate a discussion on lexical aspect of linguistics in connection with language and culture studies. This study aims to investigate frequent academic idioms used by American and British people through corpus analysis. The discussion covers analysis of idioms’ frequency per million words through BNC and COCA.